2007
DOI: 10.1111/j.1600-0420.2007.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Photopic 30 Hz flicker electroretinography predicts ocular neovascularization in central retinal vein occlusion

Abstract: ABSTRACT.Purpose: To confirm the predictive value of photopic cone b-wave implicit time in 30 Hz flicker electroretinography (ERG) for ocular neovascularization (NV) in central retinal vein occlusion (CRVO), and to compare the ERG results to the presumed healthy fellow eye. Methods: A retrospective analysis of 71 consecutive patients with CRVO. After ERG examination, all patients were followed for at least 12 months, or until NV was found. Three patients died during the study period; none of the other patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…5). Changes in 30-Hz flicker have been described in other retinal diseases [15][16][17]. These studies may indicate that an increased 30-Hz flicker implicit time indicates damaged cone function of the entire retina, either in the form of ischaemia or in the form of a detached retina.…”
Section: Discussionmentioning
confidence: 94%
“…5). Changes in 30-Hz flicker have been described in other retinal diseases [15][16][17]. These studies may indicate that an increased 30-Hz flicker implicit time indicates damaged cone function of the entire retina, either in the form of ischaemia or in the form of a detached retina.…”
Section: Discussionmentioning
confidence: 94%
“…Retinal ischemia was studied in 18 of the patients in this study using the cone b-wave implicit time in the 30 Hz flicker ERG. There is evidence that the cone implicit times in the 30 Hz flicker ERG are the most predictive ERG parameter for the development of neovascularization in the eyes with CRVO [44-47]. …”
Section: Discussionmentioning
confidence: 99%
“…The risk of neovascular complications in patients with CRVO is related to the extent of capillary nonperfusion or the degree of retinal ischemia, and can be evaluated with fluorescein angiography (FA) [41-43], but several recent studies have demonstrated that full-field electroretinography (ERG) could be a more suitable method of identifying ocular ischaemia, especially the cone b-wave implicit time, in both photopic and scotopic 30 Hz flicker ERG [44-47]. The cone b-wave implicit times in the 30 Hz flicker ERG have been found to be the most predictive ERG parameter for the development of ocular neovascularization [45], and were found to be significantly correlated with the concentration of vascular endothelial growth factor (VEGF) in the aqueous in CRVO patients [48].…”
Section: Introductionmentioning
confidence: 99%
“…Morrell et al found that the interocular difference in the flicker ERG latency was the significant distinguishing factor [17]. Kjeka et al found that the latency was the significant factor, but interocular difference was of less value [11]. Larsson et al found that the implicit time, but not the amplitude of 30-Hz flicker ERG was a good predictor of rubeosis in CRVO patients [15].…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, most papers have focused on the investigation of brief protocol for busy clinical practices [11,14,15,26]. Flicker ERG has the benefits of simplicity, not subjected to photomyoclonic reflex and as reliable as standard ERG.…”
Section: Discussionmentioning
confidence: 99%